Rezerwy na naprawy gwarancyjne - Jankowiak, Joanna (Reserves for guarantee repairs, 2007)
This article discloses warranty reserves for guaranteed repairs which are a specific type of liability. These reserves are essential in providing an accurate picture of a company’s financial position. By allocating warranty reserves, a company can minimize economic risks along with the financial impact of costs associated with promised repairs for which a business is truly liable. In allocating reserves, a company should consider its type of business, economic conditions, and historic trends of repairs made.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 227-238